Paraneoplastic cerebellar degeneration in a patient with a primary fallopian tube adenocarcinoma. A case report and brief review - Mario Campero; Alberto E. Selman (Elsevier, 2017)
We describe a 65-year-old woman with subacute cerebellar syndrome expressed as severe ataxia, and the presence of anti Purkinje cell antibodies (Anti-Yo). A small adnexal mass was only evident on PET CT with the pathological feature of fallopian tube adenocarcinoma. Anti-Yo antibodies have been strongly associated with paraneoplastic cerebellar degeneration, and nearly always associated to ovarian adenocarcinomas. Few cases have been reported in which this paraneoplastic syndrome has been related to fallopian tube adenocarcinoma. In this report, we discuss this association and its relation with fallopian tube and ovarian carcinoma.